2004
DOI: 10.1021/nl0489586
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Cytotoxicity of Water-Soluble Fullerenes

Abstract: We show that the cytotoxicity of water-soluble fullerene species is a sensitive function of surface derivatization; in two different human cell lines, the lethal dose of fullerene changed over 7 orders of magnitude with relatively minor alterations in fullerene structure. In particular, an aggregated form of C60, the least derivatized of the four materials, was substantially more toxic than highly soluble derivatives such as C3, Na+ 2 - 3[C60O7 - 9(OH)12 - 15](2-3)-, and C60(OH)24. Oxidative damage to the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
761
10
8

Year Published

2006
2006
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 999 publications
(820 citation statements)
references
References 62 publications
41
761
10
8
Order By: Relevance
“…This is especially noticeable from the ability of the Daphnia to recovery to pre-exposure behavior levels when exposed to C 60 HxC 70 Hx but not the suspension of nano-C 60 . Sayes et al (2004) and Chen et al (2006) showed that cytotoxicity of nanoparticles is affected by addition of functional groups. Furthermore, functional groups and sites of attachments determine the effectiveness of antifouling agents against barnacle settlement (39).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially noticeable from the ability of the Daphnia to recovery to pre-exposure behavior levels when exposed to C 60 HxC 70 Hx but not the suspension of nano-C 60 . Sayes et al (2004) and Chen et al (2006) showed that cytotoxicity of nanoparticles is affected by addition of functional groups. Furthermore, functional groups and sites of attachments determine the effectiveness of antifouling agents against barnacle settlement (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although the water-soluble fullerenes are not genotoxic (Zakharenko et al, 1997) they are retained in the body for long periods, raising concerns about chronic toxic effects (Yamago et al, 1995). Fullerol and other water soluble hydroxylated fullerenes have been found to be cytotoxic to human dermal fibroblasts, human liver carcinoma cells (HepG2) and neuronal human astrocytes (Sayes et al, 2004;Sayes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Buckministerfullerenes (fullerenes) are a class of carbon nanomaterials with biomedical, electronic, and semiconductor applications (1)(2)(3)(4). The potential environmental and health effects of fullerenes have attracted increasing attention in recent years (5)(6)(7)(8), especially with the development of water-soluble forms that facilitate their use in biological systems (3,9).…”
Section: Introductionmentioning
confidence: 99%